Effects of the 2-aminoimidazoline on rat kidney and liver - Cevik, A.; Karatas, F.; Kara, H.; Gene, M.; Koca, M. (My University, 2008)
The aim of this study was to investigate structural and biochemical changes in liver and kidney of rats treated with synthetic N- (1,3-benzothiazol - 2-yl)- N-(A,5 - dihydro-1, H-imidazol-2-yl) amine (2-Amdz). In the liver and kidney vitamin A, E, and C levels decreased significantly compared to controls (P < 0.05) whereas liver and kidney MDA levels were higher than control levels (P < 0.005). Focal mononuclear cell infiltrations, diffuse megalocytosis and cogulative necrosis were seen in the liver. In the kidneys, haemorrhages in the interstitial region and dense lymphocytosis infiltration in the cortical part were seen. As a result, it can be suggested that 2-Amdz induced a severe stress and increased the amount of free radicals and significantly decreased the levels of antioxidant and vitamins in liver and kidney.
Keywords: Rattus